2018
DOI: 10.1007/s00248-018-1255-4
|View full text |Cite
|
Sign up to set email alerts
|

Global Networks of Symbiodinium-Bacteria Within the Coral Holobiont

Abstract: Scleractinian corals form the framework of coral reefs and host abundant and diverse microbial communities that are fundamental to their success. A very limited number of studies have examined the co-occurrence of multiple partners within the coral 'holobiont' and their pattern of specificity over different geographical scales. In this study, we explored two molecular sequence datasets representing associations between corals and dinoflagellates in the genus Symbiodinium and between corals and bacteria, across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 102 publications
1
43
0
1
Order By: Relevance
“…The relationship between Symbiodiniaceae and their associated bacterial communities has been studied in significantly less detail than bacterial‐coral or Symbiodiniaceae‐coral associations (Lawson et al ., ), which is surprising given the fact that species‐specific algal‐bacterial interactions have been reported to directly or indirectly influence both partners (Bolch et al ., ). Recent work using network analysis to examine Symbiodiniaceae‐bacterial associations across water basins and coral hosts suggests complementary interactions between microbial communities that need to be considered (Bernasconi et al ., ). For example, Bernasconi et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The relationship between Symbiodiniaceae and their associated bacterial communities has been studied in significantly less detail than bacterial‐coral or Symbiodiniaceae‐coral associations (Lawson et al ., ), which is surprising given the fact that species‐specific algal‐bacterial interactions have been reported to directly or indirectly influence both partners (Bolch et al ., ). Recent work using network analysis to examine Symbiodiniaceae‐bacterial associations across water basins and coral hosts suggests complementary interactions between microbial communities that need to be considered (Bernasconi et al ., ). For example, Bernasconi et al .…”
Section: Discussionmentioning
confidence: 97%
“…For example, Bernasconi et al . () report some bacterial‐Symbiodiniaceae co‐occurrences within the coral holobiont (e.g., Vibrio ) that occur independently of phylogeny or geographic location. Within our study, no core zOTUs were shared across all Symbiodiniaceae strains, although Labrenzia and two unassigned bacteria were core genera (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have specifically considered Symbiodiniaceae‐bacterial interactions in the coral holobiont, with their results pointing to the potentially critical role that these partnerships might play in regulating holobiont nutrient cycling and competitive fitness (Ritchie, ; Bourne et al ., ; Ainsworth et al ., ; Peixoto et al ., ; Silveira et al ., ; Bernasconi et al ., ); Table ). For example, some coral‐associated bacteria can rapidly take up organosulfur compounds released by Symbiodiniaceae cells, such as dimethylsulfoniopropionate (DMSP), to sustain their growth and produce an antimicrobial compound active against common coral pathogens (Raina et al ., ; Raina et al ., ).…”
Section: Introductionmentioning
confidence: 93%
“…Numerous studies have demonstrated that both endosymbiotic Symbiodiniaceae and associated bacteria support the persistence of corals through the exchange of metabolites and bioactive compounds (Rohwer et al ., ; Cantin et al ., ; Ainsworth et al ., ; Bourne et al ., ; Glasl et al ., ; Peixoto et al ., ; Hillyer et al ., ; Matthews et al ., ). Yet, remarkably, the role of bacteria in regulating Symbiodiniaceae resource acquisition, competitive performance and functional diversity (as both free‐living and endosymbionts) is relatively unexplored (Ritchie, ; Bourne et al ., ; Ainsworth et al ., ; Peixoto et al ., ; Silveira et al ., ; Bernasconi et al ., ); Table ). This fundamental gap in knowledge wholly constrains our understanding of how microbes act in concert to regulate the health of coral holobionts, especially given the importance of bacterial‐algal interactions for nutrient cycling, signal transduction and gene transfer as demonstrated for other microalgal taxa (Seymour et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation